MENJADI GURU PENDIDIKAN JASMANI YANGTRANSFORMATIF (SEBUAH KAJIAN KRITISDAN SOLUSI KURIKULUM 2002) - Muhammad H. Anwar Caly Setiawan (Jurnal Pendidikan Jasmani Indonesia, 2006)
A curriculum is a blue print of education output. Curriculum must bring awareness to studentsof their self reality and their surroundings. If the content of the curriculum cannot conveythose awareness, it will only make education an alienation process for students. This articletries to analyze 2002 PJKR curriculum from the view of content, its logical system, andparameter of output. This analyzes refer to Fernandez Balboa writing that analyze andcompare several trends in Physical Education curriculum worldwide. From the analyzeshows that 2002 PJKR similar with traditional curriculum which emphasize on bio scientific.Positivism paradigm in 2002 PJKR can influence sensitivity of student’s analyzing skill insocial reality and social changes. This will contribute to produce students, that in the futurewill be teachers, will merely only become distribution agent of knowledge. They cannotbecome a social transformation agent. Therefore, there is need to change 2002 PJKRcurriculum to include subject matter that can train student’s critical ability and sensitivity onsocial reality.Keyword: curriculum, critical study, social reality, teacher, transformative.